Clinical psychology PhD students' admission experiences: Implications for recruiting racial/ethnic minority and LGBTQ students. Issue 1 (15th October 2020) - Hsueh, Loretta; Werntz, Alexandra; Hobaica, Steven; Owens, Sarah A.; Lumley, Mark A.; Washburn, Jason J.
Abstract: Aim: The purpose of this study was to explore differences in the clinical psychology PhD program admissions experience (i.e., interviewing and decision‐making) by race/ethnicity and lesbian, gay, bisexual, transgender, and queer (LGBTQ) identity. Methods: Participants were 803 students (24% racial/ethnic minority; 19% LGBTQ) enrolled in US clinical psychology PhD programs. Two‐group comparisons tested for differences in admission experiences by race/ethnicity and LGBTQ identity. Results: Racial/ethnic minority and LGBTQ students considered a programmatic commitment to diversity as more important in application decisions compared to non‐Hispanic White and cisgender heterosexual students, respectively. LGBTQ students were more likely to be advised to not discuss personal information (e.g., sexual orientation) than cisgender heterosexual students. Racial/ethnic minority and LGBTQ students identified financial considerations and program outcomes as more important in their decision‐making compared with non‐Hispanic White and cisgender heterosexual students, respectively. Conclusion: Increasing funding and fostering authentic training environments should be prioritized in institutional conversations around recruiting racial/ethnic minority and LGBTQ trainees.